Functional Relationships of Wood Anatomical Traits in Norway Spruce - Piermattei, Alma; von Arx, Georg; Avanzi, Camilla; Fonti, Patrick; Gärtner, Holger; Piotti, Andrea; Urbinati, Carlo; Vendramin, Giovanni Giuseppe; Büntgen, Ulf; Crivellaro, Alan (Frontiers in Plant Science, 2020)
The quantitative assessment of wood anatomical traits offers important insights into those factors that shape tree growth. While it is known that conduit diameter, cell wall thickness, and wood density vary substantially between and within species, the interconnection between wood anatomical traits, tree-ring width, tree height and age, as well as environment effects on wood anatomy remain unclear. Here, we measure and derived 65 wood anatomical traits in cross-sections of the five outermost tree rings (2008–2012) of 30 Norway spruce (Picea abies (L.) H. Karst.) trees growing along an altitudinal gradient (1400-1750 m a.s.l.) in the northern Apennines (Italy). We assess the relationship among each anatomical trait and between anatomical trait groups according to their function for i) tree-ring growth, ii) cell growth, iii) hydraulic traits, and iv) mechanical traits. The results show that tree height significantly affects wood hydraulic traits, as well as number and tangential diameter of tracheids, and ultimately the total ring width. Moreover, the amount of earlywood and latewood percentage influence wood hydraulic safety and efficiency, as well as mechanical traits. Mechanically-relevant wood anatomical traits are mainly influenced by tree age, not necessarily correlated with tree height. An additional level of complexity is also indicated by some anatomical traits, such as latewood lumen diameter and the cell wall reinforcement index, showing large inter-annual variation as a proxy of phenotypic plasticity. This study unravels the complex interconnection of tree-ring tracheid structure and identifies anatomical traits showing a large inter-individual variation and a strong interannual coherency. Knowing and quantifying anatomical variation in cells of plant stem is crucial in ecological and biological studies for an appropriate interpretation of abiotic drivers of wood formation often related to tree height and/or tree age.